1992
DOI: 10.1103/physrevlett.69.3286
|View full text |Cite
|
Sign up to set email alerts
|

First observation of magnetic moment precession of channeled particles in bent crystals

Abstract: Spin precession of channeled particles in bent crystals has been observed for the first time. Polarized I"*" were channeled using bent Si crystals. These crystals provided an effective magnetic field of 45 T which resulted in a measured spin precession of 60° ±17°. This agrees with the prediction of 62° ± 2° using the world average of Z"*" magnetic moment measurements. This new technique gives a I"*" magnetic moment of (2.40 ± 0.46 ± 0.40)/X7v, where the quoted uncertainties are statistical and systematic, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…Because of the extremely short lifetime of charmed baryons in comparison with the Σ + hyperon, in our case it is not possible to prepare a beam of polarized baryons in advance and to measure the degree of their initial polarization, as was done in the Fermilab experiment [42]. In our case, as explained below, the crystal could be used as a beam collimator.…”
Section: Spin Precession In a Bent Crystal Master Formulasmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the extremely short lifetime of charmed baryons in comparison with the Σ + hyperon, in our case it is not possible to prepare a beam of polarized baryons in advance and to measure the degree of their initial polarization, as was done in the Fermilab experiment [42]. In our case, as explained below, the crystal could be used as a beam collimator.…”
Section: Spin Precession In a Bent Crystal Master Formulasmentioning
confidence: 99%
“…The first experimental realization of such method was carried out in Fermilab [42] at the 800 GeV proton beam. The strange Σ + (uus) baryons (with lifetime 0.8×10 −10 s) produced on the Cu target had average momentum 375 GeV/c and the absolute value of polarization (12 ± 1) %.…”
Section: Jhep08(2017)120mentioning
confidence: 99%
“…So, since the distance over which it will precess through a given angle in a crystal is drastically shortened compared to in a magnet, one may use this eect to measure magnetic moments of shortlived particles. This eect has been used in a proof-of-principle experiment to measure the magnetic moment of the R [89], a hyperon with l 2X46l N and a short lifetime in its rest-system, cs 2X4 cm [90], see also [91].…”
mentioning
confidence: 99%
“…Nowadays this effect has been experimentally discovered [4,5,6]. It has been also shown that the similar experiments are beneficial for measuring the magnetic moments of short-lived particles [7] and, particularly, Λ c particle [8].…”
Section: Introductionmentioning
confidence: 99%